Rapid extraction and analysis of oxidative stress and DNA damage biomarker 8-hydroxy-2′-deoxyguanosine (8-OHdG) in urine: Application to a study with pregnant women - Bláhová, Lucie; Janoš, Tomáš; Mustieles, Vicente; Rodríguez-Carrillo, Andrea; Fernández, Mariana F.; Bláha, Luděk (International journal of hygiene and environmental health, 2023)
Oxidative stress is an important toxicity and genotoxicity mechanism of many chronic adverse health outcomes. This study developed a sensitive extraction method for urine matrix (based on lyophilization, without the need for pre-cleaning by solid phase extraction), coupled to LC-MS/MS analysis of the biomarker 8-hydroxy-2′-deoxyguanosine (8-OHdG). The methodology was validated in urine samples from a cohort of Spanish pregnant women collected during the first, second and third trimester of pregnancy, and urine samples collected within 24 h after delivery (n = 85). A detection and quantification limit of 0.01 and 0.05 μg/L, respectively, were established. The median 8-OHdG concentration was 2.18 μg/L (range 0.33–7.79); and the corresponding creatinine-adjusted concentrations ranged from 1.04 to 13.12 with median of 4.48 μg 8-OHdG/g creatinine. The concentrations of non-adjusted 8-OHdG significantly decreased (p < 0.05) in the 3rd trimester and post-delivery urine samples when compared to the 1st trimester levels. 8-OHdG concentrations were further studied in placenta samples matching the same urine samples (n = 26), with a median value of 1.3 ng 8-OHdG/g of tissue. Placental 8-OHdG concentrations were correlated with urinary levels of non-adjusted 8-OHdG in the 3rd trimester. Considering the small cohort size, results must be interpreted with caution, however statistical analyses revealed elevated urinary non-adjusted 8-OHdG levels in the 1st trimester of mothers that delivered boys compared to those who delivered girls (p < 0.01). Increased urinary non-adjusted 8-OHdG concentrations at the time of delivery were significantly associated with clinical records (any type of clinical record during pregnancy; p < 0.05). The novel extraction and analytical method for the assessment of 8-OHdG is applicable for sensitive analysis of multiple analytes or biomarkers in urine matrix. This method could also be applied for other matrices such as blood or tissues. Our findings show that 8-OHdG in urine of pregnant women could predict oxidative stress in placenta and can be related to characteristics such as maternal obesity, mode of delivery and newborn sex.